Analysis Factors of Exclusive Breastfeding in Post Partum Mothers at Hermina Hospital, Kemanyoran, Central Jakarta - Muslichah; Lail, Nurul Husnul; Azzahroh, Putri (International Journal of Midwifery and Health Sciences, 2023)
Background : Early and exclusive breastfeeding is very important for a child's survival, and to protect them from various diseases that they are susceptible to and which can be fatal. Increasing evidence shows that children who receive breast milk have higher intelligence test results. Factors that can influence exclusive breastfeeding include breast care, knowledge, attitudes, mental health and family support. Objective : To analyze the factors of exclusive breastfeeding for post partum mothers at Hermina Kemayoran Hospital, Central Jakarta. Methods : Analytical survey research using cross sectional research design with a sample of 80 people, data collection using a questionnaire, processed and analyzed using univariate and bivariate analysis. Results : The study found that most of the respondents stated that they gave exclusive breastfeeding (80.0%). Chi square analysis found breast care (p value = 0.004), knowledge (p value = 0.516), attitude (p value = 0.116), mental health (p value = 0.940), and family support (p value = 0.010). Conclusion : There is a relationship between breast care and family support with exclusive breastfeeding and there is no relationship between knowledge, attitudes and mental health with exclusive breastfeeding for post partum mothers at Hermina Kemayoran Hospital, Central Jakarta. Suggestion : perform breast care and provide family support to post partum mothers